1980
DOI: 10.1111/j.1348-0421.1980.tb02853.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of Elements in Ashed Spores of Bacillus megaterium

Abstract: The structure of the skeleton of spores of Bacillus megaterium was examined after ashing in a plasma asher and the elemental composition of the ashed whole spores was determined with an analytical electron microscope. All spores were ashed in situ although they shrank by about 15%. Even P and S, in addition to metals, were recovered well from ashed samples. Ash was rich in the core and the coat, and poor in the cortex. Ca, P, S, and Mg were detected in the core and coat of the spore of B. megaterium QM B 1551.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Calcium distribution studies using high-resolution electron probe X-ray microanalysis (15,23,24,35) revealed that only a fraction of the total spore calcium was detected in the integuments. The bulk portion (> 98-99%) of the spore calcium was found in the core region.…”
Section: Restoration By Calcium Of L-alanine-induced Germinabilities mentioning
confidence: 99%
See 2 more Smart Citations
“…Calcium distribution studies using high-resolution electron probe X-ray microanalysis (15,23,24,35) revealed that only a fraction of the total spore calcium was detected in the integuments. The bulk portion (> 98-99%) of the spore calcium was found in the core region.…”
Section: Restoration By Calcium Of L-alanine-induced Germinabilities mentioning
confidence: 99%
“…Only a small fraction of the total spore calcium is believed to be associated with the spore integuments, i.e., coat and cortex (23,24). The function of this integumentassociated calcium is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate which might come from phospho-galactosamine and muramate in the outer coat (5) should be the main strong acidic group of the spore surface, and the negative charge should be neutralized with calcium, magnesium, and other metals, located in the coat of the native spores (6). The increase in germinability of the low P-spores and the Ca-spores, and the decrease in germinability of the acid-washed spores (9) indicate that the negative charge might block the action of ionic germinants and act as a barrier against the initiation of germination.…”
Section: Discussionmentioning
confidence: 99%
“…Following treatment of polymyxin B-treated and gentamicin-treated spores with CaC12 dissociated these antibiotics from the spore coat (6) and reversed their inhibitory effect on growth (13). It is wellknown that bacterial spores contain a large amount of calcium released during germination (8,9). In the present paper, we examined the amount of polymyxin B released from polymyxin B-treated spores upon germination and by treatment with Effect of Polymyxin B on Growth of Germinated Spores and Young Vegetative Cells As polymyxin B did not inhibit the germination of B. subtilis dormant spores, it was considered to act directly on germinated spores.…”
mentioning
confidence: 99%